Psychological Needs and Quantity of Substance Use in Duhok City - Arezi, Musaab Abdulhafidh Zainal (ASANKA : Journal of Social Science and Education, 2025)
This study aimed to examine the psychological needs of substance abusers in Duhok City, Kurdistan Region of Iraq, using a mixed-methods approach to analyze 47 incarcerated individuals in the adult male and female reformatory of Duhok, and also collected official records from 2018 to 2024 related to substance convictions and individuals who visit health sectors with the intention of treatment. The assessment tools contained six psychological domains through semi-structured questionnaires to be analyzed for measuring the psychological needs. Participants reported significantly lower levels of psychological needs than expected (39.543 vs. 41.5, p < 0.05), with self-esteem being significantly affected and competence being less affected. Males reported stronger social bonds than females. Quantitative analysis revealed significant increases in substance-related convictions: adult males increased from 40 (2018) to 494 (2022) and 228 (from Jan to Jul 2024), totaling 1,830 convictions. The number of females who were convicted due to drugs is 138, while juvenile males recorded are 122, among 11–17-year-olds who are trafficking and consuming drugs. Treatment pathways have shown a shift from public to private health care. Azadi Hospital's cases have decreased from 160 (2019) to 90 in 2023 and only 20 (from Jan to Jul 2024), while private clinics treated over 1,000 patients annually. These findings highlight the urgent need for comprehensive psychological interventions that address low self-esteem, gender-specific programs, fill the psychological needs, and improve access to healthcare to address the region's worsening substance abuse crisis.